Five Myths about Internationalization - Knight, Jane (International Higher Education, 2011)
Five myths about internationalization are explored. A common element of each myths is that the benefits of internationalization or the degree of internationality can be measured quantitatively. The purpose of identifying and reflecting on these myths and truths is to ensure that internationalization is on the right track and that we, as higher education sectors, are aware of intended and unintended consequences.